From porphyrin benzylphosphoramidate conjugates to the catalytic hydrogenation of 5,10,15,20-tetrakis(pentafluorophenyl)porphyrin - de Souza, Marcos C.; Pedrosa, Leandro F.; Cazagrande, Géssica S.; Ferreira, Vitor F.; Neves, Maria G. P. M. S.; Cavaleiro, José A. S. (Beilstein Journal of Organic Chemistry, 2014)
Three new porphyrin aminoalkyl dibenzylphosphoramidates were synthesized by nucleophilic aromatic substitution of one p-fluorine atom of 5,10,15,20-tetrakis(pentafluorophenyl)porphyrin (TPPF20) by primary aminoalkyl dibenzylphosphoramidates. The nucleophilic aromatic substitution was promoted by microwave irradiation in N-methyl-2-pyrrolidinone. Attempts to remove the benzyl groups of the phosphoramidate moiety by hydrogenolysis with 10% Pd/C led to the cleavage of the P–N bond and the reduction of the macrocycle to hydroporphyrin-type derivatives. The extent of the effect of the catalytic hydrogenation to TPPF20 with 10% Pd/C was then studied with a variety of solvents. The results showed that ethanol/DMF is the solvent of choice to produce chlorin TPCF20 and an ethanol/DMF/NEt3 mixture is more adequate to produce isobacteriochlorin (TPIF20).
Keywords: catalytic hydrogenation; chlorin; isobacteriochlorin; phosphoramidate; porphyrin

Chemical Aspects of Photodynamic Therapy - Bonnett, R. (Gordon and Breach Science Publishers, 2000)

The Porphyrin Handbook - Pandey, R. K.; Zheng, G. (Academic Press, 2000)

(untitled) - Börjesson, K.; Wiberg, J.; El-Sagheer, A. H.; Ljungdahl, T.; Martensson, J.; Brown, T.; Nordén, B.; Albinsson, B. (ACS Nano, 2010)

(untitled) - Pedrosa, L. F.; Souza, M. C.; Faustino, M. A. F.; Neves, M. G. P. M. S.; Silva, A. M. S.; Tomé, A. C.; Ferreira, V. F.; Cavaleiro, J. A. S. (Aust. J. Chem., 2011)

(untitled) - Behrmanm, E. J.; Biallash, M. J.; Brass, H. J.; Edwards, J. O.; Saks, M. (J. Org. Chem., 1970)

(untitled) - Borbas, K. E.; Kee, H. L.; Chandrashaker, V.; Muthiah, C.; Holten, D.; Lindsey, J. S. (J. Org. Chem., 2008)

(untitled) - Costa, J. I. T.; Tomé, A. C.; Neves, M. G. P. M. S.; Cavaleiro, J. A. S. (J. Porphyrins Phthalocyanines, 2011)

(untitled) - de Souza, M. C.; de Macedo, W. P.; Torres, T. S.; Pedrosa, L. F.; Alt, H. G. (Phosphorus, Sulfur Silicon Relat. Elem., 2006)

(untitled) - Samaroo, D.; Soll, C. E.; Todaro, L. J.; Drain, C. M. (Org. Lett., 2006)

(untitled) - Clark, V. M.; Kirby, G. W.; Todd, A. (J. Chem. Soc., 1958)

(untitled) - Galezowski, M.; Gryko, D. T. (Curr. Org. Chem., 2007)

(untitled) - Lipinska, M. E.; Teixeira, D. M. D.; Laia, C. A. T.; Silva, A. M. G.; Rebelo, S. L. H.; Freire, C. (Tetrahedron Lett., 2013)

(untitled) - Brigas, A. F.; Costa, A. M. R.; Serra, A. C.; Pires, C. (J. Pharm. BioAllied Sci., 2011)

(untitled) - Schlesinger, W.; Corwin, A. H.; Sargent, L. J. (J. Am. Chem. Soc., 1950)

(untitled) - Whitlock, H. W.; Hanauer, R.; Oester, M. Y.; Bower, B. K. (J. Am. Chem. Soc., 1969)

(untitled) - Bonnett, R.; White, R. D.; Winfield, U.; Berenbaum, M. C. (Biochem. J., 1989)

(untitled) - Pereira, M. M.; Abreu, A. R.; Goncalves, N. P. F.; Calvete, M. J. F.; Simões, A. V. C.; Monteiro, C. J. P.; Arnaut, L. G.; Eusébio, M. E.; Canotilho, J. (Green Chem., 2012)

(untitled) - Arabei, S. M.; Kulikov, S. G.; Veret-Lemarinier, A. V.; Galaup, J. P. (Chem. Phys., 1997)

(untitled) - Kulikov, S. G.; Veret-Lemarinier, A. V.; Galaup, J. P.; Chaput, F.; Boilot, J. P. (Chem. Phys., 1997)

(untitled) - Bergonia, H. A.; Phillips, J. D.; Kushner, J. P. (Anal. Biochem., 2009)